WAYS TO IMPROVE INVENTORY MANAGEMENT (IMPROVEMENTS IN INVENTORY MANAGEMENT) IN THE DIGITAL ECONOMY - Ovlayev Sukhrob Temur oglu; Batirjonova Bonu Bakhtiyor's kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This scientific article examines the methodological foundations of improving accounting in the context of digitalization. The introduction of modern information technologies is analyzed as an important factor in increasing the efficiency of accounting processes, ensuring the reliability and transparency of information. In the context of the digital economy, the need for automation of accounting systems, electronic data exchange and the use of integrated information systems in enterprises is increasing. The study highlights the limitations of traditional accounting methods and ways to improve them based on digital technologies. The impact of the digitalization process on the quality, speed of accounting and management decision-making is also analyzed.